SEKTOR INFORMAL DAN URGENSI PENATAANNYA DI KOTA SAMARINDA - dan Baban Sobandi, Tri Widodo W. Utomo (Jurnal Borneo Administrator, 2007)
The existence and expansion of informal sector in a city with rapid economic growth is just a natural thing. From many sources and experiences, informal sector shows significant and increasing role in underpinning socio-economic life of a society. Moreover, in many cases, it can be functioned as “safety net” system during deteriorating economic stability. Unfortunately, government’s attention to make its competitiveness better seems to be doubtfully planned and managed. Instead of providing sound policy, informal sector is often seen as one of the main causes in producing city problems such as waste disposal, traffic congestion, city stoutness, etc. This paper serves the general profile of informal sector in Samarinda City, and possible recommendation to be implemented in the near future in order to create a new city with more vivid, humanizing, and friendly approach.  Keywords: Sektor Informal, Kota Samarinda.